Effect of roller pressure and base prepreg layer on tensile and flexural properties of CFRP laminates fabricated using automated fiber placement - Mathew, Eldho (2023)
Composites can be manufactured in numerous ways. Among the available methods, Automated Fiber Placement (AFP) is the most advanced and latest technology utilized by companies for aerospace and other projects. Although it offers many benefits, it has unique manufacturing challenges and quality issues. The presence of tow placement defects such as tow gaps, tow overlaps, twisted tows, incomplete tows, and missing tows in the AFP process are causes for concern as these lead to a decrease in the mechanical performance of the fabricated parts. Although it is not possible to completely avoid the occurrence of defects, optimizing key process parameters is a possible way to minimize them. Roller pressure is one such parameter. If it is too high, it can lead to wider and thinner tows and if it is too low, the towpreg may not stick properly to the substrate and hence, not conform to curvatures. In this work, test layups of different configurations using carbon (T700SC-24K-50C) towpreg with epoxy (UF 3376-100) as the matrix system were prepared at different compaction roller pressures (2 bar, 3.5 bar, and 5 bar), with and without the presence of base prepreg layers. Tensile and bending tests were respectively carried out according to ASTM D3039 and ASTM D7264 to study the effects of these process parameters on the layup defects. From the test results, it is found that using a compaction roller pressure of 3.5 bar and a base prepreg layer of the same material as the towpreg, leads to minimum defects, and hence, to the best tensile and bending properties.